Evidence of differential genetic introgression at multiple localities between Neotoma floridana and N. micropus - Vrla, Sarah C.; Mauldin, Matthew R.; Haynie, Michelle L.; Bradley, Robert D. (THERYA, 2021)
To determine the extent of genetic introgression along the parapatric border between Neotoma floridana and N. micropus, 140 woodrats were sampled from 21 localities in Kansas, Oklahoma, and Texas, at varying distances from the proposed species boundaries. All individuals were examined at the mitochondrial cytochrome-b gene (Cytb) and two nuclear introns: intron seven of the Beta fibrinogen gene (Fgb-I7) and intron 2 of the vertebrate alcohol dehydrogenase gene (Adh1-I2). Additionally, individuals from a putative contact zone were genotyped using six microsatellite loci to better analyze population structure. Evidence of mixed ancestry was detected in 55 of 140 (39 %) individuals, at 10 of 21 (48 %) localities up to 150 km from the proposed parapatric boundary. A pattern of differential admixture detected between the two nuclear markers suggested variation in selection pressures at the Adh1-I2 and Fgb-I7 markers is dependent upon the genomic makeup of the individual. Together, the mitochondrial and nuclear markers indicate evidence of historical hybridization and suggest that hybrid zones within this system are transient in nature.